2017
DOI: 10.1093/mmy/myx029
|View full text |Cite|
|
Sign up to set email alerts
|

Epidemiology and clinical characteristics of invasive mould infections: A multicenter, retrospective analysis in five Asian countries

Abstract: Formal, large-scale, multicenter studies of invasive mould infection (IMI) in Asia are rare. This 1-year, retrospective study was designed to assess the incidence and clinical determinants of IMI in centers in five countries (Thailand, Taiwan, Singapore, China, India). Patients treated in a single year (2012) were identified through discharge diagnoses, microbiology, and histopathology logs, and entered based on published definitions of IMI. A total of 155 cases were included (median age 54 years; 47.7% male).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 30 publications
0
28
1
1
Order By: Relevance
“…There is heightened concern about invasive mould infections (IMIs) as a consequence of the increasing number of immunocompromised patients (Lass-Flörl and Cuenca-Estrella, 2017;Rotjanapan et al, 2018). Fusaria are among the most frequent cause of IMIs after aspergilli (Nucci and Anaissie, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is heightened concern about invasive mould infections (IMIs) as a consequence of the increasing number of immunocompromised patients (Lass-Flörl and Cuenca-Estrella, 2017;Rotjanapan et al, 2018). Fusaria are among the most frequent cause of IMIs after aspergilli (Nucci and Anaissie, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Most Fusarium species have low susceptibilities to the majority of azole antifungals (Tupaki-Sreepurna et al, 2017;Rotjanapan et al, 2018;Herkert et al, 2019) and patients with IFs have high mortality rates (Esnakula et al, 2013;Silva et al, 2013;Okada et al, 2018). Voriconazole (VRC) and amphotericin B (AMB) are the recommended treatment options for localised infections and IFs (Efeİris et al, 2016;Okada et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Clinical symptoms typically manifest as fever, cough, dyspnea, chest pain, and hemoptysis; 7,8 however, these characteristics only present in some patients. Radiologic examination of the lungs of these patients showed various presentations, only a few had typical features of fungal infection, such as denseness, cavitation, an air crescent sign (11%), or a halo sign (4.1%~7%); 8,9 some even showed negative results (15%). 10 The 1.3-ß-D-glucan (BG) test is used to detect the BG antigen, which is commonly resides on the fungal surface.…”
Section: Introductionmentioning
confidence: 99%
“…A large-scale international multicenter study conducted by Tacoone et al investigated ICU patient with IA and found that older age, bone marrow transplant, higher sequential organ failure assessment (SOFA) score, mechanical ventilation use and requirement for renal replacement therapy were predictors of a poor outcome [ 1 ]. Another multicenter study by Porpon et al evaluated the epidemiology of invasive mold infection in five Asian countries and concluded that disseminated diseases, rheumatologic condition and higher GM levels were predictors of mortality [ 8 ]. Since there is no overall consensus, it is necessary to have more evidence regarding prognostic factors to identify patients with IPA who are at a higher risk of mortality.…”
Section: Introductionmentioning
confidence: 99%